2010
DOI: 10.2967/jnumed.109.068098
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of Incorporating Time-of-Flight Information into Clinical PET/CT Imaging

Abstract: The introduction of fast scintillators with good stopping power for 511-keV photons has renewed interest in time-of-flight (TOF) PET. The ability to measure the difference between the arrival times of a pair of photons originating from positron annihilation improves the image signal-to-noise ratio (SNR). The level of improvement depends upon the extent and distribution of the positron activity and the time resolution of the PET scanner. While specific estimates can be made for phantom imaging, the impact of TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
180
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 14 publications
10
180
2
Order By: Relevance
“…The TOF information provides a difference in arrival times between a pair of coincident photons and narrows the probability that the annihilation event will be located along the line of response. This additional information enables the reconstruction algorithm to converge to the expected image with fewer iterations and a better noise level (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TOF information provides a difference in arrival times between a pair of coincident photons and narrows the probability that the annihilation event will be located along the line of response. This additional information enables the reconstruction algorithm to converge to the expected image with fewer iterations and a better noise level (18).…”
mentioning
confidence: 99%
“…Recent studies have reported faster convergence of lesion contrast and improvements in lesion detection performance with TOF (18)(19)(20)(21)(22). However, the effects of PSF and TOF have not been sufficiently demonstrated in different reconstruction parameters or investigated for their effects on noise levels.…”
mentioning
confidence: 99%
“…Use of FDG-PET/CT for detection of the primary tumor is currently not recommended, mainly because of the supposedly low sensitivity for small carcinomas. However, the introduction of TOF technology used in this research has further increased the image quality of PET/CT and dramatically improved cancer detectability [25]. In a recent study, 67% of T1b and 98% of T1c tumors could be visualized with PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Including time-of-flight (TOF) information in PET reconstruction has been shown to improve clinical PET images [1]- [3]. A variety of reconstruction approaches exist for threedimensional (3D) TOF-PET data.…”
Section: Introductionmentioning
confidence: 99%
“…2 in [19], one can estimate the maximum angular interval (α max ) that provides adequate sampling consistent with the spatial resolution of the data as (1) In this calculation, FWHM LOR is defined by the detector spatial resolution rather than the pixel size as was done in [19]. The subsequent minimum number of transverse angular samples (nϕ min ) and tilt angles (nθ min ) can be calculated from (2) (3) where θ max is the full axial angular range of the scanner. For a whole-body TOF-PET scanner with 6-mm resolution and 430-ps timing resolution, only 17 transverse angular samples and 2 oblique tilt angles are required; for a scanner with 700-ps timing resolution, 28 transverse views and 3 oblique tilt angles are needed.…”
Section: Introductionmentioning
confidence: 99%